Chapter Twenty-six Syriac Medicine - Kessel, Grigory (Taylor & Francis, 2019)
The field of Syriac medicine is perhaps one of the least investigated and explored domains within Syriac intellectual culture. Yet owing to its decisive role during the late antique period for the transfer of Greek medical knowledge to the Islamic world, it should occupy a very special position, and the results of its study are appealing to both Classicists and historians of Greek and Islamic medicine. The study of Syriac medicine deals predominantly with medical literature, but also with theory and practice as they evolved over centuries within changing social and historical contexts (the surveys available differ in perspective and scope: Gignoux 2001a ; Habbi 2001 ; Muraviev 2014 ; Pormann and Savage-Smith 2007 : 17-21; Strohmaier 1994 ; on the Syriac scholarly milieu more broadly: Debié 2014 ).